Development of pyridine-based inhibitors for the human vaccinia-related kinases 1 and 2 - Serafim, R; De Souza Gama, F; Dutra, L; Dos Reis, C; Vasconcelos, S; Da Silva Santiago, A; Takarada, J; Di Pillo, F; Azevedo, H; Mascarello, A; Elkins, J; Massirer, K; et al. (American Chemical Society, 2019)
Vaccinia-related kinases 1 and 2 (VRK1 and VRK2) are human Ser/Thr protein kinases associated with increased cell division and neurological disorders. Nevertheless, the cellular functions of these proteins are not fully understood. Despite their therapeutic potential, there are no potent and specific inhibitors available for VRK1 or VRK2. We report here the discovery and elaboration of an aminopyridine scaffold as a basis for VRK1 and VRK2 inhibitors. The most potent compound for VRK1 (26) displayed an IC50 value of 150 nM and was fairly selective in a panel of 48 human kinases (selectivity score S(50%) of 0.04). Differences in compound binding mode and substituent preferences between the two VRKs were identified by the structure-activity relationship combined with the crystallographic analysis of key compounds. We expect our results to serve as a starting point for the design of more specific and potent inhibitors against each of the two VRKs.